Perspectives on health, illness, disease and management approaches among Baganda traditional spiritual healers in Central Uganda. - Yahaya H K Sekagya; Charles Muchunguzi; Payyappallimana Unnikrishnan; Edgar M Mulogo (Public Library of Science (PLoS), 2024)
In Uganda, spirituality is closely associated with traditional healthcare; however, though prevalent, it is considered controversial, mystical, less documented and often misunderstood. There is a paucity of literature on the description of health, illness, disease, and management approaches among traditional spiritual healers. This article examines the perspectives on health, illness, disease, and management approaches among Baganda traditional spiritual healers, the Balubaale, in Central Uganda, who engage ancestral spirits during health care and management. We used a qualitative study design in particular grounded theory. We used semi-structured, qualitative interviews and observation on 12 male and female purposively selected Balubaale in Central Uganda. Data was transcribed, coded, and thematically analyzed using ATLAS ti. 22 Computer software based on an inductive approach. Findings show that the words and concepts describing health, illness, disease, and management approaches are descriptive and contextualized to include the problem, the prospected root-causes, and the therapeutic approaches involved. The words for illness "olumbe", disease "obulwadde" and the management approaches such as divination (kulagula), ritual cleansing (kwambulula), amulets (ensiriba and yirizi), and scarification (kusandaga) have spiritual and social dimensions, contextual meanings and attachments. Further research is recommended among other tribes and larger sample size to compare findings and terminologies to facilitate communication and policy considerations.